ELECTRO OPTIC MODULATOR DEVICES FOR HIGH SPEED DATA IN OPTICAL COMMUNICATION - Raghunathababu; P, Siddaiah (International Journal of Research -GRANTHAALAYAH, 2015)
Electro Optic devices in fiber optic Communication systems are playing a Vital Role in telecommunication infrastructure for worldwide broadband networks. Wide bandwidth of signal transmission with low delay, wide transmission bandwidth with less latency, the transmission medium for long distance with high data rate transmission. This paper gives an overview of Electro optic devices for fiber optic systems and their key technologies, their technological trend towards the next generation.